Analisis Break Even Point pada PT Maju Bersama (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Break Even Point (BEP) analysis is a method to determine the point where total revenue equals total costs, which is the basis for business decision making. This study examines BEP at PT Maju Bersama, a palm oil plantation company. The definition of BEP includes fixed costs and variable costs associated with production. Assumptions in determining BEP include stability of selling price per unit, consistency of production costs, and no significant changes in market demand. The calculation results show that PT Maju Bersama needs to produce a certain number of units to reach the break-even point. Thus, this analysis provides valuable insight for management in planning production strategies and cost control, as well as increasing the company's profitability in the future.